Influence of light curing source on microhardness of composite resins of different shades Influência da fonte de luz polimerizadora na microdureza da resina composta de diferentes cores - André Luiz Fraga Briso; Tânia Maria Fedel; Sibéria de Morais Pereira; Sílvio José Mauro; Renato Herman Sundfeld; Maria Lúcia Marçal Mazza Sundefeld (University of São Paulo, 2006)
INTRODUCTION: The evolution of light curing units can be noticed by the different systems recently introduced. The technology of LED units promises longer lifetime, without heating and with production of specific light for activation of camphorquinone. However, further studies are still required to check the real curing effectiveness of these units. PURPOSE: This study evaluated the microhardness of 4 shades (B-0.5, B-1, B-2 and B-3) of composite resin Filtek Z-250 (3M ESPE) after light curing with 4 light sources, being one halogen (Ultralux - Dabi Atlante) and three LED (Ultraled - Dabi Atlante, Ultrablue - DMC and Elipar Freelight - 3M ESPE). METHODS: 192 specimens were distributed into 16 groups, and materials were inserted in a single increment in cylindrical templates measuring 4mm x 4mm and light cured as recommended by the manufacturer. Then, they were submitted to microhardness test on the top and bottom aspects of the cylinders. RESULTS: The hardness values achieved were submitted to analysis of variance and to Tukey test at 5% confidence level. It was observed that microhardness of specimens varied according to the shade of the material and light sources employed. The LED appliance emitting greater light intensity provided the highest hardness values with shade B-0.5, allowing the best curing. On the other hand, appliances with low light intensity were the least effective. It was also observed that the bottom of specimens was more sensitive to changes in shade. CONCLUSION: Light intensity of LED light curing units is fundamental for their good functioning, especially when applied in resins with darker shades. INTRODUCTION: A evolução dos aparelhos fotopolimerizadores pode ser notada nos diferentes sistemas introduzidos recentemente no mercado. A tecnologia apresentada pelos aparelhos LED promete maior tempo de vida útil, não gerar aquecimento e produzir luz específica para a ativação da canforoquinona. No entanto, ainda são necessários estudos complementares para se conhecer a real efetividade destes aparelhos na polimerização dos materiais. PROPOSTA: Neste trabalho foi verificada a microdureza de 4 cores (B-0,5, B-1, B-2 e B-3) da resina composta Filtek Z-250 (3M ESPE) quando polimerizadas com 4 fontes de luz, sendo uma halógena (Ultralux - Dabi Atlante) e três LED (Ultraled - Dabi Atlante, Ultrablue - DMC e Elipar Freelight - 3M ESPE). MÉTODOS: Os 192 corpos-de-prova foram distribuídos em 16 grupos e os materiais foram inseridos em único incremento em matrizes cilíndricas de 4mm X 4mm, sendo polimerizados pelo tempo preconizado pelo fabricante. Em seguida, foram submetidos ao teste de microdureza na superfície superior e inferior dos cilindros. RESULTADOS: Os valores de dureza obtidos foram submetidos à análise de variância e ao teste de Tukey ao nível de 5%. Foi observado que a dureza dos corpos-de-prova variou conforme a cor do material e aparelhos utilizados. O aparelho LED que emite maior intensidade luminosa proporcionou a obtenção dos maiores valores de dureza, com o croma B-0,5 possibilitando a melhor polimerização. Por outro lado aparelhos com baixa intensidade luminosa foram os menos efetivos. Também foi observado que a região do fundo dos corpos-de-prova foi mais sensível à mudança das cores. CONCLUSÕES: A intensidade de luz dos fotopolimerizadores LED é fundamental para seu bom funcionamento, principalmente quando empregadas resinas com croma mais acentuado.